Aplikasi Pembaca Dongeng Anak Indonesia Berbasis Android - Astrid Aprillini; R. Rizal Isnanto; Rinta Kridalukmana (Jurnal Teknologi dan Sistem Komputer, 2015)
Currently, to obtain information about fairy tales through a mobile phone is still rare. Readers usually obtain information about fairy tales only through books, CDs or other print media. Of multiple applications on a mobile phone that is only text and images. So the purpose of this study was achieved to help the reader enjoy fairy tales exist in a complicated application without having to read one each one word at story. This study used Luther as a method of multimedia development. There are 6 steps being taken to complete this application, namely the concept stage, design stage, collection materials, manufacture stage, testing stage and distribution. In the testing phase used two kinds of testing, ie testing functions and testing program using the respondents. The results show that “Aplikasi Pembaca Dongeng Anak Indonesia” can display information includes the title story of Indonesian children stories, national origin story, and the story is short but interesting. Can also be a sound and background music on each page of the story based on the story. And the application can be used by users with ease. Based on the results of the questionnaire showed that the data processed 91.76% positive response or included in the category of "Good".